Angiotensin-Converting Enzyme Inhibition Attenuates Lipopolysaccharide-Induced Lung Injury by Regulating the Balance Between Angiotensin-Converting Enzyme and Angiotensin-Converting Enzyme 2 and Inhibiting Mitogen-Activated Protein Kinase Activation. Issue 4 (April 2015) - Li, Yingchuan; Zeng, Zhen; Li, Yachun; Huang, Weifeng; Zhou, Ming; Zhang, Xiaoli; Jiang, Wei
<x xml:space="preserve">Abstract</x> ABSTRACT Activation of the renin-angiotensin system (angiotensin-converting enzyme [ACE]/angiotensin II [Ang II] and angiotensin-converting enzyme 2 [ACE2]/Ang-1–7) has been implicated in the pathophysiology of inflammatory response and acute lung injury (ALI). Previous studies have shown that the ACE inhibitor captopril (Cap) may be a potent therapeutic drug for ALI. However, the mechanisms of its protective effects on ALI are still largely unknown. In this study, we evaluated the effects of Cap on preventing lipopolysaccharide (LPS)–induced lung injury and further investigated the underlying mechanisms of these protective effects. Rats were intraperitoneally pretreated with Cap (50 mg/kg) 30 min prior to an intravenous administration of LPS (7.5 mg/kg). Furthermore, following a 30-min pretreatment with Cap (10−5 mol/mL) or combined with the ACE2 inhibitor MLN4760 (10−7 mol/mL), rat pulmonary microvascular endothelial cells (PMVECs) were stimulated with LPS (1 mg/mL). Captopril pretreatment significantly attenuated LPS-induced pathophysiological changes in the lung, inhibited secretion of tumor necrosis factor α and interleukin 6, reduced the ratio of Ang II to Ang-1–7, and reversed the increased ratio of ACE to ACE2, which was remarkably decreased from 7.07 (LPS only) to 1.71 (LPS + Cap). The protective effects of Cap on ALI were also confirmed by in vitro studies, in which Cap suppressed LPS-induced secretion of proinflammatory cytokines and modulated the expression levels of ACE and ACE2. After Cap pretreatment, the ratio of ACE to ACE2 expression was remarkably decreased from 5.18 (LPS alone) to 1.52 (LPS + Cap). Furthermore, Cap given before LPS administration led to inhibition of p38 mitogen-activated protein kinase (MAPK), ERK (extracellular signal-regulated kinase) 1/2, and JNK (c-Jun N-terminal kinase) phosphorylation in PMVECs, whereas MLN4760 abolished the protective effects of Cap on LPS-induced secretion of proinflammatory cytokines and abolished Cap-induced blockade of p38MAPK, ERK1/2, and JNK phosphorylation. Our findings reveal that Cap exerts protective effects on LPS-induced lung injury and the cytotoxicity of PMVECs, and these effects may, at least in part, regulate the balance of ACE and ACE2 expression and inhibit the activation of MAPKs.